The impact of government spending on the private sector : crowding-out versus crowding-in effects - Furceri, Davide (2011)
The aim of this paper is to analyze the impact of government spending on the private sector, assessing the existence of crowding-out versus crowding-in effects. Using a panel of 145 countries from 1960 to 2007, the results suggest that government spending produces important crowding-out effects, by negatively affecting both private consumption and investment. Moreover, while the effects do not seem to depend on the different phases of economic cycle, they vary considerably among regions. The results are economically and statistically significant, and robust to several econometric techniques.